Respuesta :

261561

Answer:

x= -4

Step-by-step explanation:

Simplifying

5x + -4 = 7x + 4

Solving

-4 + 5x = 4 + 7x

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.

-4 + 5x + -7x = 4 + 7x + -7x

Combine like terms: 5x + -7x = -2x

-4 + -2x = 4 + 7x + -7x

Combine like terms: 7x + -7x = 0

-4 + -2x = 4 + 0

-4 + -2x = 4

Add '4' to each side of the equation.

-4 + 4 + -2x = 4 + 4

Combine like terms: -4 + 4 = 0

0 + -2x = 4 + 4

-2x = 4 + 4

Combine like terms: 4 + 4 = 8

-2x = 8

Divide each side by '-2'.

x = -4

Simplifying

x = -4